The impact of demographics on the prevalence and treatment of type 2 diabetes - a literature review - Gadziński, Patryk; Czechowicz, Marta; Madoń, Joanna (Journal of Education, Health and Sport, 2025)
Background Type 2 Diabetes is, without a doubt, a global health crisis. Detailed guidelines have been made to create a universal standard for prevention, screening, and therapy, but far too often, a single model proves inefficient in treating patients from all walks of life, displaying a wide variance in both clinical and lifestyle factors. Aim This review of the existing literature attempts to showcase the main differences in the prevalence, risk factors, and therapy effectiveness of Type 2 Diabetes between a number of demographics. Materials and Methods The article thoroughly reviews the existing literature on Type 2 Diabetes and the demographic factors thereof. Original studies, reviews, meta-analyses, as well as epidemiological surveys available in the PubMed and Google Scholar databases were included. The literature review and article selection process concluded in November 2025. Results The available data backs up the hypothesis that demographic factors heavily influence the prevalence and outcomes of Type 2 Diabetes. The illness is both more prevalent and on average, more poorly controlled in women, as compared to men, resulting in a higher all-cause mortality. In terms of age, each additional year at the time of diagnosis correlates with a 4% decrease in all-cause mortality, as well as a 3% decrease in macrovascular and 5% decrease in microvascular complications. Additionally, socioeconomic factors have been found to play a significant role in therapy adherence, even in countries with a well-developed social safety net. Conclusions The findings showcase a desperate need for a more personalized approach to Type 2 Diabetes, focusing on the elimination of negative lifestyle habits, a thorough patient education, and a choice of medication that is within an acceptable financial range, rather than simply prescribing that, which displays the highest effectiveness on paper.